Extended-Spectrum β-Lactamase- and Carbapenemase-Producing Enterobacteriaceae Isolated from Egyptian Patients with Suspected Blood Stream Infection. - H M Abdallah; B B Wintermans; E A Reuland; A Koek; N al Naiemi; A M Ammar; A A Mohamed; C M J E Vandenbroucke-Grauls (PLoS ONE, 2015)
The aim of the study was to investigate the prevalence of extended-spectrum β-lactamase and carbapenemase production among Enterobacteriaceae isolated from Egyptian patients with suspected blood stream infection.Ninety-four Enterobacteriaceae blood culture isolates from Egyptian patients with suspected blood stream infection were collected, one isolate per patient. Identification of bacterial isolates was performed with MALDI-TOF (MS-based Vitek MS system, bioMerieux). Screening for ESBLs and carbapenemases production was done with the Vitek 2 system (bioMérieux). ESBL production was confirmed using the combined disk diffusion method for cefotaxime, ceftazidime, and cefepime, all with and without clavulanic acid (Rosco). Real-time PCR and sequencing were used to characterize the resistance genes. The phylogenetic groups of E. coli were identified by a PCR-based method.Of the 94 Enterobacteriaceae isolates 46 (48.93%) showed an ESBL phenotype. One Enterobacter spp isolate was ESBL-producer and meropenem-resistant. The genetic analysis showed that CTX-M was present in 89.13% (41/46) of the ESBL-producing Enterobacteriaceae, whereas TEM and SHV were detected in 56.52% (26/46) and 21.74% (10/46) respectively (47.83%) of the ESBL-producing isolates were multidrug resistant (MDR). Eleven out of 30 ESBL-producing E-coli isolates were assigned to phylogroup B2, followed by groups B1 (8 isolates), A (6 isolates) and D (5 isolates).The high ESBL-E rates (48.93%) found in this study together with the identification of one carbapenem-resistant Enterobacter spp isolate is worrisome. Our results indicate that systems for monitoring and detection of ESBL-producing bacteria in Egyptian hospitals have to be established. Also strict hospital infection control policies with the restriction of the consumption of extended-spectrum cephalosporins are necessary.